Study on the construction wastes generation at Kuala Terengganu - Noor Rahimah, Mamat (2018)
Nowadays, the increasing quantity of municipal solid waste has causes serious environmental problem which requires a better solution in handling the wastes that generate. Construction waste is considered as part of the municipal solid waste. Construction wastes that produce in the construction process contributes a large amount to municipal solid waste. For that reason, a proper way of handling construction wastes is significance in reducing the negative impacts towards the environment, social, and economy. This first objective of the study is to estimate the quantity of waste generation at selected construction sites near Kuala Terengganu. Other than that, this study also to investigate the current practices or C&D waste management on sites. Lastly the objective of this research is to identify the strategies taken by the companies in minimizing waste at construction sites. Quantitative method is used as a data collections for this study. This is related with taken a sampling from a certain population. For this study, questionnaire had been given to the 32 person from 32 sites. The responded to questionnaire about total estimated waste generated, method of disposing and the method how the managed the waste. Survey information was obtained through the respond from reviewer and all responses remained confidential. Descriptive statistics were used to analyse the data.. From the survey, there a few types of waste found during the all phase of construction. The most commons five of type of waste generated at selected 32 constructions sites are wood (26%), followed by steel 23%, brick 22%, concrete 18% and lastly plastic (11%). Besides, the respondents believed that there are a few factors which contribute to the waste generation. However, the respondents agreed that design changes during the construction phase contribute the highest factor of waste generation. Most of the sites managed to disposed the waste by sending the waste to the disposal centre which are lefal in Malaysia. The legal landfill in Kuala Terengganu is located at Kampung Sungai Ikan, Terengganu and Sungai Kerak, Marang A few action has been taken in order in minimizing waste. the respondents believed that the worker should cut the material like steel reinforcements, timber or pipes properly to reduce the waste. Lastly, it is essential for the contractors to follow Site Waste Management Plans (SWMPs) in order to manage the construction waste more effectively.